Los límites de la legítima defensa : ¿podemos matar aun cuando existe la posibilidad segura de huir? - Kenny, Patricio Enrique (2015)
Inquiring ourselves about the limits of the legitimate right to self-defense imply acknowledging its basis. These limits may interfere when examining the victim?s duty to scape when there?s an unlawful attack.